Acclimation of tomato plants to salinity stress after a salicylic acid pre-treatment - Tari, Irma (Acta Biologica Szegediensis, 2002)
Long-term incubation of tomato plants in low concentration of salicylic acid enabled plants to tolerate salt stress caused by 100 mM NaCI. Na+ ions accumulated in the leaf tissues of treated plants and functioned as osmolytes without the well-known detrimental effects of the excess sodium.